A Pilot Study of Serum Parathyroid Hormone in Acute Coronary Syndrome - Hoque, Md Harisul; Zaman, SM Mustafa; Ahmed, Khurshid; Kabir, Md Faisal Ibne; Fatema, Nilufar (University Heart Journal, 2020)
Acute coronary syndrome (ACS) is the public health issue as it is the single most common cause of death in the world. Role of vitamin D in cardiovascular health is of much interest at present. Experimental, as well as, some observational studies suggest that vitamin D and its metabolites are integrally related to blood pressure and the rennin-angiotensin system. Vitamin D insufficiency affects almost 50% of the population worldwide. Few studies have been carried out to determine the prevalence of hypovitaminosis D in Bangladesh . 30 Patient with ACS were included in this study who had admitted in the department of Cardiology of Bangabandhu Sheikh Mujib Medical University (BSMMU) patient with in first 48 hours of the onset of chest pain. This study was conducted from 1st July’18 to 30th June’19 (One year) by Purposive sampling. Data analysis was carried out by using the statistical package for Social Science (SPSS) version 20.0 windows software. Baseline characteristics have been compared using the independent sample student t-test test where appropriate. The student t-test was used to assess the correlation between PTH levels. p-value <0.05 was taken as significant. We found an association between elevated PTH levels and ACS. University Heart Journal Vol. 16, No. 2, Jul 2020; 71-77